14q13 distal microdeletion encompassing NKX2‐1 and PAX9: Patient report and refinement of the associated phenotype. Issue 7 (5th May 2016) - Gentile, Mattia; De Mattia, Delia; Pansini, Angela; Schettini, Federico; Buonadonna, Antonia Lucia; Capozza, Manuela; Ficarella, Romina; Laforgia, Nicola
Abstract : Chromosome 14q11‐q22 deletion syndrome (OMIM 613457) is a rare genomic disorder whose associated phenotype is heterogeneous, depending on the size, and, mostly, on the deleted region. We report the clinical and molecular characterization of a female newborn, whose phenotype was characterized by poor growth, dysmorphic facial features, subclinical hypothyroidism, and mild reduction of CD3CD8 Lymphocytes with increased CD4/CD8 ratio. By array‐CGH, we identified a 4.08 de novo interstitial deletion of the 14q13.2q21.1 region, which includes 16 OMIM genes.Our patient phenotype is compared with other published cases, for a better classification of the 14q11‐q22 deletion syndrome. We demonstrated that the 14q13.2q21.1 deletion, which encompasses NKX2‐1, but not FOXG1 gene and HPE8 region, identifies a well defined, more benign, microdeletion syndrome. This report confirms that an early identification with accurate characterization of the genomic disorders is of great relevance, enabling proper genetic counseling of the reproductive risk, as well as disease prognosis, and patient management. © 2016 Wiley Periodicals, Inc.